The Effect of Comparison of Online Consumer Review Information on Online Purchases at Online Supermarkets Through Customer Value as An Intervening Variable - Agus Rizal; Bambang Purwoko; Mombang Sihite; Derriawan Derriawan (Budapest International Research and Critics University, 2022)
Online shopping has now become one of the social phenomena that are happening in the community, many of which start switching and are interested in the online shop to meet the needs of the community in daily needs. The fulfillment of the needs of the core community, namely the purchase of daily need such as raw vegetables, raw meat, raw herbs, and a staple core of the other community. The fulfillment of these needs is facilitated by advances in information and communication in providing basic needs with the online supermarket through customer value to achieve the increase in purchases at the online supermarket. This study aims to test, review and analyze to know, a picture of the influence of online customer review, e-service quality, equity, and brand value of customers of the online purchase for partial and customer value as a mediator in influencing the online purchase in DKI Jakarta. The results showed all significant variables that proved the influence of online customer review, e-service quality, and equity of the brand to online purchase with the total contribution of the influence of zero-point fifty-nine or fifty-nine percent of the results the most significant effect of e-service quality on online purchase the two other variables. While the online customer review, e-service quality, equity brands synergy with the value customers proved a positive and significant effect on online purchasing with the contribution of the zero point fifty-four or fifty-four percent of e-service quality influence on online purchase. Among the four variables that influence the online purchase has a value of dominant e-service quality. Thus, the value of the customer proved to be able to mediate the strengthening of the influence of online purchase online supermarkets.